Estetika Struktural Sastra Dakwah Dalam Bidadari Untuk Dewa Karya Asma Nadia - Nurul Ara'af Gunawan; Mahli Zainuddin (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
This study discusses Nadia's Asma da'wah messages in the Bidadari Untuk Dewa novel and how the delivery of da'wah messages in the story. This research is a study that uses a qualitative approach and discourse analysis of the Van Dijk model. The source of this research is in the form of library literature. The results of this study state that the preaching message contained in this novel covers aspects of aqeedah, sharia, and morality. Aspects of aqeedah include tawakkal, piety and istiqomah values. Sharia aspects include sholat, mu'amalah, and prayer. Then the moral aspects include patience, sincerity, grateful gratitude, humility and honesty. From the thematic side, it was found that the title of Bidadari untuk Dewa was taken from a true story. This story illustrates the story of the journey of a young man who decides to do business and get married at a relatively young age and has to face various life problems ranging from financial, debt, business studies, female exams, friendship, and even almost losing his life at the age of 5 years. In the storyline, this novel is the longest novel Asma Nadia that she has written during her career in the world of writing. That is all due to the